Regional Economic Outlook, May 2005, Sub-Saharan Africa. (Regional Economic Outlook, 2005)
Regional Economic Outlook: Sub-Saharan Africa Prepared by the Policy Wing of the IMF African Department, this first, annual issue of Regional Economic Outlook: Sub-Saharan Africa analyzes economic, trade, and institutional issues in 2004, and prospects in 2005, for the 42 countries covered by the Department (for data reasons, Eritrea and Liberia are excluded). Topics examined include responses to exogenous shocks, growth performance and growth-enhancing policies, and the effectiveness of regional trade arrangements. Detailed aggregate and country data (as of February 24, 2005) are provided in an appendix and a statistical appendix, and a list of relevant publications by the African Department is included.